A Study of Performance of Compressed Earth Brick Incorporation with Waste Fire Clay Brick as a Filler - Mohd Yassin, Nurain Izzati; Burhanudin, Mohd Khairy; Ekhwan, Nur Ilmiah Izzah; Hadipramana, Josef (International Journal of Sustainable Construction Engineering and Technology, 2023)
This study examines the use of waste fire clay brick as a filler in compressed earth brick production. The purpose of this study is to determine the compressive strength and water absorption of the compressed earth brick incorporation with waste fire clay brick as a filler. The optimum amount of waste fire clay to utilize as a filler is also being studied. A total of 72 compressed earth bricks were produced with the brick size of 125 mm x 250 mm x 100 mm which consist of a mix of sand, soil and cement with mix proportion of 1:4:4. A few tests were conducted which are compressive strength test and water absorption test. The waste fire clay bricks were utilized in this study and replace by volume fraction percentage of 10%, 20%, 30%, 40% and 50% while 0% is set as the control. The findings obtained show that the compressive strength of the bricks was increasing. The percentage of water absorption were decreasing along with the increases of percentage of waste fire clay brick as a filler.